Relationship between green management and environmental training in companies located in Brazil: A theoretical framework and case studies - Teixeira, Adriano Alves [UNESP]; Chiappetta Jabbour, Charbel Jose [UNESP]; Lopes de Sousa Jabbour, Ana Beatriz [UNESP] (Elsevier B.V., 2012)
The main objective of this study is to understand the relationship between green management and environmental training in Brazilian companies, underscoring how this relationship takes place and its most important factors. For such, 9 case studies were conducted at large ISO 14001 certified companies, leaders in their market segments. Several interviews were conducted for each case, documents were collected and visits were made for direct observation. The main contributions and results of this study were: (a) a proposal for a theoretical framework relating the evolutionary stages of green management and the characteristics of environmental training; (b) it was ascertained, as per the proposed theoretical framework, that organizational culture and teamwork, top management support and more technical green management practices are the factors that seem to connect and convert environmental training into more proactive green management, especially for companies in the proactive green management stage; (c) the identification of the co-evolution between the companies' stage of green management and their environmental training level, which is the identified relationship mechanism between environmental training and green management. In other words, the higher the level of adoption of activities recommended for green management, the more evolved the green management practiced at the companies tends to be; and (d) identification that the proposed theoretical framework tends to be useful, mainly because it can explain the relationship between green management and environmental training at the company in the proactive stage. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Environmental training; Green management; Human resources; Brazil